The Effect of External Technology Cooperation and Internal Relation on Innovative Behavior in Technology Intensive Organizations - Il Lee, Won; ., . (International Journal of Engineering and Technology, 2018)
This study set up a research model based on theoretical research as a study of the effects of external technology cooperation activities and internal relationship competencies on innovation behavior in high technology companies. Based on the research model, hypotheses were set up and tested through questionnaires. The research hypothesis is largely based on the internal and external cooperative activities of companies and the effect of the introduction of open innovation on innovation behavior. H1. The more internal cooperation activities in the enterprise, the more innovative behavior will occur. H2. The more active external cooperation activities within the enterprise, the more innovative behavior will occur. H3. The more internal collaborative activities and external cooperation in the enterprise, the more open innovation will be active. In this paper, I propose that internal cooperative activities, external collaborative activities, and establishment of an open innovation culture are important variables that influence innovation behavior.Â Â